PRE-SERVICE EFL TEACHERS’ REFLECTIONS: THE CONTRIBUTION OF TEACHING PRACTICUM ON ACADEMIC SUCCESS AND SELF-IMPROVEMENT - Can, Dilek Tüfekçi (PEOPLE: International Journal of Social Sciences, 2019)
Teaching practicum, which provides great opportunity for pre-service English as a Foreign Language (EFL) teachers to observe, experience and practice the knowledge they have gained theoretically in practical basis, has had a critical role in preparing the pre-service teachers with the skills they required for teaching at real classroom settings. As the research on teaching practicum indicated that there is a significant gap between the theory and practice in EFL education, this study was carried out to explore whether teaching practicum contributed to the pre-service EFL teachers’ academic success and additionally, whether teaching practicum contributed to their self-improvement as prospective teachers of English. The sample group of the current study consisted of 25 EFL pre-service teachers studying their last year at ELT department at Balikesir University in the 2016-2017 education year in Turkey. In this qualitative study, the data were obtained from a background questionnaire, reflective writings of EFL pre-service teachers and face to face interviews. The participants were interrogated to identify their reflections on the contribution of teaching practicum to their academic success and self-improvement as prospective teachers. In this study, the findings were analyzed qualitatively and discussed in the light of related literature.